Analisis Yuridis Penerapan Pasal 55 Kitab Undang-Undang Hukum Pidana sebagai Pertanggungjawaban Pidana terhadap Anak Buah Kapal Pelaku Tindak Pidana Perikanan - Alpi Sahari; Suriadi (CV. Creative Tugu Pena, 2024)
Article 55 Paragraph 1 to 1 of the Indonesian Criminal Code (KUHP) states that those who commit, order, and participate in committing the act are convicted as perpetrators of criminal acts. This includes the Master and Crew of Boath in Illegal Fishing related to fishing without a permit, using fake permits, using prohibited fishing gear, and catching species of fish that do not comply with the permit. The research problems in this study are: 1) What is the legal system in fisheries crimes? 2) How is the law enforcement against Article 55 of the Indonesian Criminal Code in the supervisory function in marine and fisheries resources? 3) What is the criminal liability for boat crews who commit fisheries crimes? This study is normative legal research with a statute approach in conducting the study. The data collection techniques used were library research. Based on the results of the study, data on illegal fishing in the fishing sector handled regarding the evidence of boats being burned, sunk, and/or destroyed in Marine and Fisheries Resources Surveillance (PSDKP) of Batam City of 2022, 2023, dan 2024 show that there are eighteen (18) units of boats with Malaysia, Myanmar, and Vietnam flags that have been sunk with other supporting facilities and equipment in committing illegal fishing, such as purse seine, trawl, fishing lights, hand line, GPS Samsung, HF Transceiver VX-1700, Radio Sea Eagle 6900, Compass Express, and navigation and communication tool. Tanjung Pinang District Court of 2024 with Case Number: 1/Pid.Sus-PRK/2023/PN TPG dan No. Case: 2/Pid.Sus-PRK/2023/PN TPG. The verdict has been a permanent legal force by prosecuting the Master and Crew of the Boat as the Defendant of Fisheries Crimes.